Levetiracetam Induced Behavioral Abnormalities in a Patient with Seizure Disorder: A Diagnostic Challenge. (18th August 2020) - Ogunsakin, Oluwaseun; Tumenta, Terence; Louis-Jean, Scarlet; Mahbub, Ayesha; Rabel, Peterson; Olupona, Tolu; Alam, Shaheen
Abstract : Levetiracetam is a second-generation antiepileptic drug that is chemically unrelated to other antiepileptic drugs. Levetiracetam is a broad-spectrum antiseizure medication that is approved as an adjunctive therapy in the treatment of partial and generalized tonic-clonic seizures in children and adults with epilepsy. The mechanism by which Levetiracetam induces behavioral changes remains unknown. Its proposed mechanism of action involves binding to synaptic vesicle protein 2A (SV2A) and this leads to neuronal inhibition. Though, the drug has a convenient dosing regimen and is relatively well tolerated, neuropsychiatric side effects can emerge beyond the initial titration period and may be the most common reason for drug discontinuation. Levetiracetam has been reported to cause varying degrees of psychiatric adverse effects including behavioral disturbance such as agitation, hostility and psychosis, and mood symptoms and suicidality. It has been shown to induce psychiatric side effects in 13.3% of adults, with only 0.7% presenting with severe symptoms such as depression, agitation, or hostility. The prevalence rate of development of psychosis in these patients is estimated to be about 1.4%. A review of literature has demonstrated a relative correlation between Levetiracetam use and the development of neurobehavioral symptoms which is increased in predisposed individuals. This research describes the case of a 28-year-old woman with seizure disorder and a psychiatric history of schizoaffective disorder who developed aggressive behavior, paranoia, and severe hostility following administration of Levetiracetam 750 mg orally twice daily. She developed acute behavioral symptoms which were reversed with cessation of Levetiracetam. This report emphasizes the need for developing an appropriately high index of suspicion in promoting surveillance and prompt identification of behavioral adverse effects associated with Levetiracetam especially in high-risk patient population.